Comparing the Effectiveness of Training Emotion Regulation Skills Based on Gross and Linehan Models on Emotion Regulation Strategies in Adolescents with Borderline Personality Disorder - سیده سامرا حسینی امام; محمود نجفی; شاهرخ مکوند حسینی; مژگان صلواتی; علی محمد رضایی (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2017)
Aim and Background: The purpose of the study was to compare the effectiveness of emotion regulation skills training based on Gross and Linehan models on emotion regulation strategies in adolescents with borderline personality disorder. Methods and Materials: This was a quasi-experiment study with pretest/posttest method and control group. The study population included all the adolescents with borderline personality disorder referred to counseling centers, psychiatrists, and psychiatric services, as well as suicide emergency centers in Tehran City, Iran, in the year 2017. 45 patients were selected using random sampling method, and were randomly divided into two experimental groups and one control group (n = 15). Both experimental groups were under treatment within 8 sessions, 2 sessions of 90 minutes weekly, while the control group received no treatment. The research tool included Cognitive Emotion Regulation Questionnaire (CERQ), which was conducted in pretest and posttest assessments. Findings: Linehan model had significant effects on all emotion regulation strategies in posttest survey. Gross model had significant effects on some of emotion regulation strategies such as acceptance, positive refocusing, refocus on planning, positive reappraisal, putting into perspective, catastrophizing, other-blame, except self-blame, and rumination in posttest assessment. Conclusions: Due to common components of treatment, both models of emotion regulation skills training were effective on emotion regulation strategies. Overall, the results indicated Linehan model to be more effective on emotion regulation strategies (reduction of less adaptive strategies). Therefore, it can be used to improve emotion regulation strategies.